2022
DOI: 10.2147/ijgm.s347178
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors, Characteristics, and Outcome in Non-Ventilated Patients with Spontaneous Pneumothorax or Pneumomediastinum Associated with SARS-CoV-2 Infection

Abstract: Background and Objectives: Spontaneous pneumothorax (SP) and spontaneous pneumomediastinum (SPM) have frequently been cited as complications associated with coronavirus disease 2019 (COVID-19) pneumonia, with especially poor prognosis in mechanically ventilated patients. The current literature is controversial regarding the potential risk factors for developing SP or SPM (SP-SPM) in non-ventilated COVID-19 patients. Our research addressed a twofold objective: (a) to investigate the characteristics of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 37 publications
3
12
0
5
Order By: Relevance
“…We developed an independent dataset with the same inclusion/exclusion criteria for external validation. First, authors who published retrospective studies in 2022 were approached, and their data were included [ 10 , 11 , 12 , 13 ]. Second, authors who reported COVID-19-related PNx/PMEx were contacted and encouraged to share data.…”
Section: Discussionmentioning
confidence: 99%
“…We developed an independent dataset with the same inclusion/exclusion criteria for external validation. First, authors who published retrospective studies in 2022 were approached, and their data were included [ 10 , 11 , 12 , 13 ]. Second, authors who reported COVID-19-related PNx/PMEx were contacted and encouraged to share data.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, el barotrauma no es una condición necesaria para que pueda producirse NMMD. De hecho, muchos pacientes con neumonía por SARS-CoV-2 que desarrollaron NMMD no habían requerido de ventilación mecánica previamente a la aparición del NMMD, por lo que en estos el barotrauma no pudo intervenir de ninguna manera en el desarrollo del NMMD (NMMD espontáneo) 12,[14][15][16][30][31][32][33]38,39 .…”
Section: Nmmd Solounclassified
“…En el caso de NMMD en el seno de COVID-19, el síntoma más frecuente es la disnea (93,3% 38 , 90,9% 7 , 62,3% 23 ) o la tos seca (85,7% 23 , 74,2% 7 , 63,3% 38 ), seguido del dolor torácico (43,3% 38 , 21,4% 23 , 19,7% 7 , 11,9% 9 ), lo cual es también comprensible dado que se trata de pacientes con diagnóstico de neumonía por SARS-CoV-2. La disnea marcada, la fiebre elevada, la taquipnea, el tiraje y la desaturación son manifestaciones que se explican más bien por la neumonía por SARS-CoV-2 en sí que por el NMMD asociado.…”
Section: Clínica De Neumomediastinounclassified
See 2 more Smart Citations